Structured learning diary and epistemic beliefs predict academic achievement in higher education - Kivimäki, Ville (Frontiers in Education, 2023)
Introduction: Epistemic cognition, which explores how knowledge is acquired, applied, and critically evaluated, is closely linked to learning. However, despite numerous studies from various perspectives, much remains to be learned about this essential and predominantly positive connection. Despite the positive connection between epistemic cognition and learning, epistemic measures have not been widely used in predicting students’ academic achievement. One possible reason for this is the difficulties in measuring personal epistemology. However, in the last decade, learning analytics has emerged as a field of study and practice with new means to collect data on different psychological constructs. This study focused on a learning analytics tool, a structured learning diary, that can support student learning while being used to record student thinking. This study explores the connection of student diaries with academic achievement, students’ epistemic beliefs’ connection with academic achievement, and the viability of implementing an epistemic belief questionnaire and a structured learning diary in a naturalistic degree program setting (N = 105). Methods: Connections between these and academic achievement were investigated at four temporal measurement points. The first aim was to test which measures of the diary tool correlated with academic achievement. The second aim was to test epistemic beliefs' correlation (Pearson correlation coefficient) with academic achievement. Models of linear regression were then designed and tested at different times. The overarching general aim of the study was to fill the gap in the use of reflective learning diaries in engineering education and epistemic beliefs in predicting academic achievement. Results and discussion: The results show that we should collect student-originated learning process data for the best predictive power and connect that with independent psychological measures. Despite the significant effort required to use the learning diaries, the results indicate that with further design, digital journaling tools are viable learning and measurement tools to be used at scale and for long periods. Future studies should investigate the possibility implement epistemic measures with structured learning diaries more closely and study the connections between diary use and personal epistemology.